The search for the distinctively human good ”“ Ethica Eudemia 1217a18-40 - Sousa, André Luiz Cruz (Revista Archai, 2017)
The paper studies the discussion about human good in Eudemian Ethics I.7. It is particularly concerned with the existence, in the text, of two characteristics of the human good: its peculiarity, on the one hand, which consists not only in the qualification ‘human’ (anthropinon), but also in the assignment of this good to the domain of action (the activity that distinguishes humans from other beings), and, on the other hand, the fact that it belongs to a spectrum containing the goods of other beings, like god and the remaining living beings. Divinity works as the standard for the distinction between eudaimonic goods ”“ belonging to beings whose nature implies participation in the divine (humans, for example) ”“ and non-eudaimonic goods that belong to those beings deprived of such participation. Resorting to other passages from the Eudemian Ethics, as well as other texts from the corpus, the paper defends that the two characteristics of the human good presented in EE I.7 foreshadow an important difference between the two Aristotelian treatises on eudaimonia: whereas the Nicomachean Ethics emphasizes contemplation as the activity through which humans participate in the divine, the Eudemian Ethics stresses virtuous actions as a human activity related to the divine.